Chicken feather protein hydrolysate as a low cost peptone source for microbial cultivation: A promising perspective of economic and environmental advantage - Getachew Alamnie; Addisu Melake; Yeshambel Berhanu; Marye Alemu; Bogale Damtew; Aleka Aemiro (Case Studies in Chemical and Environmental Engineering, 2024)
Peptones are one of the priciest culture components utilized in the cultivation of microorganisms. The objective of this work was to prepare feather hydrolysate peptone from chicken feathers using Bacillus subtilis ES5 (GenBank: OQ034477). The cell growth performances of all investigated microorganisms were shown to exhibit better results with feather hydrolysate peptone (FHP) in comparison to commercial peptone. As per the current findings, microbial-based FHP preparation is significantly less expensive than commercial peptones, and the suggested process provides cost-effective and eco-friendly solutions. Furthermore, the present investigation demonstrated opening the door to the prospect of converting chicken feather waste to peptone.